O TEMPO GRAMATICAL E OS ESCAPES DA TEMPORALIDADE: uma investigação sobre o aspecto verbal nas questões de interpretação no livro didático de Língua Portuguesa do Ensino Médio - MORAES, Maria Regina Coelho Costa (2024)
This research is based on the interpretation of time in the reading process. It starts from formal aspects of linguistic description, based on the intrinsic past, present and future network that constitutes human existence, considering elements other than just the mode-temporal ending of verbs. It goes beyond the linguistic, considering that the past is concluded in part, the present is the time from which the enunciator locates what has happened and what will happen, knowing that these meanings are hypothetical, not always chronological, because they involve physical time (Benveniste, 2006) that crosses the being in the affective synthesis of events. This is a qualitative, exploratory, descriptive and interpretative study that includes the category of time in its linguistic (TIME) and extralinguistic (TIME) dimensions: philosophical and poetic, spaces that reject the threshold of forms and quantities because they restrict the analysis of the human and social sciences. The aim of this paper is to present an investigative study of time through the lens of linguistic description as a sign of temporality, investigating it in interpretation exercises in high school Portuguese language textbooks, starting with the verbs that most commonly appear with the task of situating the communication process in time (Corôa, 2005). This is a functionalist theme, since it goes beyond verbal forms or morphemes and seeks to reach other areas of the language game (Almeida, 2020), discussed under the concept of grammaticalization based on the concept of grammar (Neves, 2002). It covers Linguistic Description, Applied Linguistics and Indisciplinary Applied Linguistics. The main authors that make up the theoretical framework are the following: Bosi (1977), Neves (2002, 2007, 2010, 2014), Corôa (2005), Benveniste (2006), Abraçado (2020), Fiorin (2021), Ilari and Basso (2014), Castilho (2014), Travaglia (2016), Ricoeur (2010), Mari (2008). We have the hypothesis that, for the reading process, it is not enough to know the verb tenses, but to be able to extrapolate to the temporality that permeates the intricacies of the meanings of a text that need to be produced and not just calculated (Mari, 2008). As a result of this research, we hope to answer whether the textbook, in its interpretation questions, deals only with the conjugation of the verbal tense or extrapolates to the aspect, a manifestation of TIME (Castilho, 2007), a place of temporality, in which the facts move outside or inside the character in the transition between chronic time and physical time.